Análises do desempenho térmico de transformadores alimentando cargas não lineares - Camargo, Jelson Machado de (2005)
This dissertation presents and analyzes the results of theoretical investigations and experimental of the thermal behavior of transformers the dry, isolated with resin epoxy, under conditions sinusoidal and non sinusoidal of tension and current. Development a study of the losses in the several parts of the transformer, standing out the losses for currents parasites proposed by the norm ANSI/IEEE [3] and was compared with other [5], more exact, that takes in consideration the geometry of the transformer. Inside of this context present new equations for the temperature elevations, rendiment, useful life and derating of the transformer. A thermal model is used to estimate the temperature elevations in the transformer. Experimental studies are led in a prototype of a transformer trifásico the dry, isolated with resin epoxy, delta/estrela, 5 kVA especially built for the accomplishment of temperature tests, with sensor thermal located in several points of the equipment. This procedure makes possible the comparison among the results computations, with views to the validation of the proposal of the thermal modelling of first order.